Intelligent Interactive Multimedia Systems and Services 2017 - De Pietro, Giuseppe; Gallo, Luigi; Howlett, Robert J.; Jain, Lakhmi C.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book constitutes the refereed proceedings of the Tenth International KES Conference on Intelligent Interactive Multimedia Systems and Services: IIMSS-17. It includes 57 full papers organized into topical sections, ranging from visual data processing to big data analytics, and from multimedia to intelligent and cognitive systems. The conference took place as part of the Smart Digital Futures 2017 multi-theme conference, held in Vilamoura, Algarve, Portugal on 21-23 June 2017, which brings together AMSTA, IDT, InHorizons, InMed, SEEL and IIMSS in one venue. It provided an international forum for researchers and scientists to share their work and experiences in the field of multimedia and intelligent interactive systems and services.
Hand-designed local image descriptors vs. off -the-shelf CNN-based features for texture classification: an experimental comparison -- Images selection and best descriptor combination for multi-shot person re-identification -- Dimensionality reduction strategies for CNN-based classification of histopathological images -- Optimizing multiresolution segmentation for extracting plastic greenhouses from WorldView-3 imagery -- Greenhouse detection using aerial orthophoto and digital surface model -- A recommender system for multimedia art collections -- Autonomous systems research embedded in teaching -- Educational assessment: Pupils' experience in primary school (Arabic grammar in 7th year in Tunisia) -- Approximate algorithm for multi-source skyline queries on decentralized remote spatial databases -- Evaluation of the criteria and indicators that determine quality in higher education: a questionnaire proposal -- Toward a Personalized recommender system for learning activities in the context ofMOOCs. .
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence